Lemma 30.26.5. Let $S$ be a scheme. Let $f : X \to Y$ be a morphism of schemes which are locally of finite type over $S$.

1. If $Y$ is separated over $S$ and $Z \subset X$ is a closed subset proper over $S$, then $f(Z)$ is a closed subset of $Y$ proper over $S$.

2. If $f$ is universally closed and $Z \subset X$ is a closed subset proper over $S$, then $f(Z)$ is a closed subset of $Y$ proper over $S$.

3. If $f$ is proper and $Z \subset Y$ is a closed subset proper over $S$, then $f^{-1}(Z)$ is a closed subset of $X$ proper over $S$.

Proof. Proof of (1). Assume $Y$ is separated over $S$ and $Z \subset X$ is a closed subset proper over $S$. Endow $Z$ with the reduced induced closed subscheme structure and apply Morphisms, Lemma 29.41.10 to $Z \to Y$ over $S$ to conclude.

Proof of (2). Assume $f$ is universally closed and $Z \subset X$ is a closed subset proper over $S$. Endow $Z$ and $Z' = f(Z)$ with their reduced induced closed subscheme structures. We obtain an induced morphism $Z \to Z'$. Denote $Z'' = f^{-1}(Z')$ the scheme theoretic inverse image (Schemes, Definition 26.17.7). Then $Z'' \to Z'$ is universally closed as a base change of $f$ (Morphisms, Lemma 29.41.5). Hence $Z \to Z'$ is universally closed as a composition of the closed immersion $Z \to Z''$ and $Z'' \to Z'$ (Morphisms, Lemmas 29.41.6 and 29.41.4). We conclude that $Z' \to S$ is separated by Morphisms, Lemma 29.41.11. Since $Z \to S$ is quasi-compact and $Z \to Z'$ is surjective we see that $Z' \to S$ is quasi-compact. Since $Z' \to S$ is the composition of $Z' \to Y$ and $Y \to S$ we see that $Z' \to S$ is locally of finite type (Morphisms, Lemmas 29.15.5 and 29.15.3). Finally, since $Z \to S$ is universally closed, we see that the same thing is true for $Z' \to S$ by Morphisms, Lemma 29.41.9. This finishes the proof.

Proof of (3). Assume $f$ is proper and $Z \subset Y$ is a closed subset proper over $S$. Endow $Z$ with the reduced induced closed subscheme structure. Denote $Z' = f^{-1}(Z)$ the scheme theoretic inverse image (Schemes, Definition 26.17.7). Then $Z' \to Z$ is proper as a base change of $f$ (Morphisms, Lemma 29.41.5). Whence $Z' \to S$ is proper as the composition of $Z' \to Z$ and $Z \to S$ (Morphisms, Lemma 29.41.4). This finishes the proof. $\square$

In your comment you can use Markdown and LaTeX style mathematics (enclose it like $\pi$). A preview option is available if you wish to see how it works out (just click on the eye in the toolbar).